Critical evaluation and thermodynamic optimization of the Li-O, and Li2O-SiO2 systems. Issue 5 (May 2017) - Konar, Bikram; Van Ende, Marie-Aline; Jung, In-Ho
Abstract: A critical evaluation and thermodynamic optimization of all available experimental data of the Li-O and Li2 O-SiO2 systems were performed to obtain one set of consistent Gibbs energy functions for all phases in the systems. The obtained Gibbs energy functions can reproduce all available and reliable experimental data from 298 K to above liquidus temperatures at one atm total pressure. It is the first time, to the best of our knowledge that the Gibbs energy of stoichiometric phases like Li2 O, Li4 SiO4, Li2 SiO3, and Li2 Si2 O5 was comprehensively evaluated and optimized. The liquid oxide solution was modeled using the Modified Quasichemical Model to describe its thermodynamic behavior accurately considering the short range ordering. Discrepancies observed in the metastable liquid immiscibility and the liquidus in the SiO2 -rich region of the Li2 O-SiO2 system was resolved. The phase diagram and thermodynamic data of all the solid and liquid phases were well reproduced within experimental error limits.